Applying CFD Technology to Determine the Effect of Two New Designed Fan Inlet Distortion Generators. (2015) - Zhipeng, Li; Chao, Lu; Hui, Wu; Xiaopeng, Liu; Guowang, Zhang
Abstract: Inlet distortion is a main resource of performance decreasing of compressor, in this way it is essential to judge the influence of inlet distortion to the compressor performance according to the test. A properly designed distortion generator can simulate the practical distortion condition exactly, which is a key and foundation to a successful distortion test. A new designed distortion generation requires proper methods for assessing the effect, while the naissance and development of computational fluid dynamics (CFD) provide an easy and effective way for this purpose. In this article two kinds of steam injectors were introduced for a fan steam injection test as distortion generator, and CFD technology was applied to simulate the effect of the schemes in order to obtain the flow field at test article inlet, and based on which the schemes were analyzed and examined. The better one was chosen from the two to make preparation for the final test. The test result will be used as a criterion to judge and modify the simulation project, then with the optimized distortion generator, a more proper test scheme will be erected.